NANOTEKNOLOGI UNTUK KEBERLANJUTAN - Mutaqin Mutaqin; Abd Mujahid Hamdan; Yunasar; Sri Indah Setiyaningsih (Jurnal Bionatural, 2025)
Nanotechnology provides innovative pathways to integrate nanotechnology with sustainability, aiding in the realization of the Sustainable Development Goals (SDGs) while tackling critical global issues. This review delves into fundamental principles and practical applications of nanotechnology, including advancements in clean energy, pollution mitigation, water purification, and sustainable agriculture. It also addresses key challenges such as regulatory hurdles, ethical considerations, safety concerns, and technological constraints. Looking ahead, fostering interdisciplinary collaboration and implementing supportive policies are vital to promoting the sustainable adoption of nanotechnology and expediting progress toward the SDGs. We aspire for this review to encourage forward-thinking, environmentally conscious research and policy initiatives that drive meaningful change.